The Importance of Surveyors and GPS Technology in Systematic Land Registration in Georgia: A Study of the Challenges and Opportunities - Tornike Merebashvili (European Scientific Journal, ESJ, 2024)
The purpose of this work is to explore the historical and contemporary importance of land registration, focusing on the crucial role played by Georgia’s surveyors. The paper concentrates on the combination of GIS-based state systems with GPS PlateTalk map registrations to resolve conflicting cadastral information as well as for accurate ownership record keeping. The Georgian absence of a unified legal and administrative framework significantly complicates land boundary delineation leading to disputes among surveyors. To standardize surveying practices and improve accuracy, an all-encompassing legal framework must be put in place.The study adopts historical, comparative legal, and hermeneutic research methods using examples from Germany and Holland that demonstrate how such advanced technologies as drones, LiDAR, and blockchain can enhance the precision, speed, and security of survey practice. Furthermore, professional education investment must be increased in both teachers and attorneys who are also informed about Geoinformation Systems (GIS), thus enabling them to perform their functions properly when it comes to law matters concerning land registers.Conclusions urge policy-makers to invest in modern technological gadgets as well as engage in legislative reforms that would make their cadastral systems stronger. That would result in the creation of robust cadastral systems by investing in modern technology as well as carrying out legal reforms that would modernize their existing cadastral systems.